DONALD T. HAWKINS, ed., Personal Archiving: Preserving Our Digital Heritage - Bass, Jordan (Archivaria, 2015)
Personal Archiving: Preserving Our Digital Heritage. DONALD T. HAWKINS, ed. Medford, NJ: Information Today, Inc., 2013. xx, 299 pp. ISBN 978-1-57387-480-9.